Pengaruh Pemberian Monosodium Glutamat pada Induk terhadap Fase Erupsi Gigi Anak Tikus Wistar (Rattus norvegicus) Generasi Pertama (The Effect of Monosodium Glutamate Administration on Mothers Rat (Rattus norvegicus) to the Tooth Eruption Phase of the Fir - Mindiya .; Didin Erma Indahyani; Pujiana Endahl Lestari (Pustaka Kesehatan, 2017)
Background: Monosodium glutamat (MSG) is a kind of food additives which consumes widely in society. It may damage the hypothalamic arcuate nucleus and disturb the endocrin regulation system. This condition may delay the tooth eruption phase. Aim: To analyze the effect of MSG administration on the neonatal rats tooth eruption phase, whose mothers were given MSG during gestational period also during gestational and lactation period, to determine the difference between neonatal male and female tooth eruption phase. Materials and Methods: The first molar of right mandibular of neonatal rats from the control group (K1), the treatment group which mothers were given MSG during pregnant period (K2) and the mothers which were given MSG during pregnant and lactation period (K3) were collected as samples. The samples were examined by periapical rontgent to observe the tooth eruption phase. The result was measured by Corel Draw X3. Results and Conclusion: The tooth eruption phase in the treatment group (K2 and K3) are slower than the control group (K1), and there is no difference between neonatal male and female tooth eruption phase. Kata Kunci: hypothalamic arcuate nucleus, monosodium glutamate, tooth eruption